2022
DOI: 10.1002/cam4.5545
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk for women with diabetes and the impact of metformin: A meta‐analysis

Abstract: Background Diabetes mellitus has been associated with increased breast cancer (BC) risk; however, the magnitude of this effect is uncertain. This study focused on BC risk for women with type 2 diabetes mellitus (T2DM). Methods Two separate meta‐analyses were conducted (1) to estimate the relative risk (RR) of BC for women with T2DM and (2) to evaluate the risk of BC for women with T2DM associated with the use of metformin, a common diabetes treatment. In addition, subgroup analyses adjusting for obesity as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…The relationship between obesity, hyperinsulinemia, T2D, menopausal status and BC is complex 55,56 . While increased adiposity in postmenopausal women associates with an increase in BC risk, obesity and T2DM appear to have either no effect or even some protective effect in premenopausal women [57][58][59][60] . 1J-K), a feature found in >80% of human BC 18,19 .…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between obesity, hyperinsulinemia, T2D, menopausal status and BC is complex 55,56 . While increased adiposity in postmenopausal women associates with an increase in BC risk, obesity and T2DM appear to have either no effect or even some protective effect in premenopausal women [57][58][59][60] . 1J-K), a feature found in >80% of human BC 18,19 .…”
Section: Discussionmentioning
confidence: 98%
“…Given that diabetes disproportionately affects low-income adults 37 and also increases the risk of breast cancer, 38 understanding the role of diabetes in adjuvant therapy for breast cancer among low-income women is critical to inform the appropriate care of this medically vulnerable patient population. In this population-based study, we comprehensively evaluated utilization, timely initiation, adherence, persistence and continuation, and/or completion of adjuvant therapies for breast cancer among Medicaid-insured women aged less than 65 years with and without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] However, the more recent literature is inconsistent, with more evidence suggesting there was no association between metformin use and breast cancer incidence. [10][11][12][13] More importantly, published studies have been conducted mainly in populations with T2D. Only three large epidemiological studies of breast cancer have included both non-T2D and T2D populations, 7,14,15 making the effect of metformin use in a general population and inter-relationship of T2D status and metformin difficult to estimate.…”
Section: Introductionmentioning
confidence: 99%
“…Several early epidemiologic studies (mostly before 2012) showed lower breast cancer incidence among metformin ever users compared with never users 5–9 . However, the more recent literature is inconsistent, with more evidence suggesting there was no association between metformin use and breast cancer incidence 10–13 . More importantly, published studies have been conducted mainly in populations with T2D.…”
Section: Introductionmentioning
confidence: 99%